2014
DOI: 10.1038/cddis.2014.386
|View full text |Cite
|
Sign up to set email alerts
|

MiR-630 inhibits proliferation by targeting CDC7 kinase, but maintains the apoptotic balance by targeting multiple modulators in human lung cancer A549 cells

Abstract: MicroRNAome analyses have shown microRNA-630 (miR-630) to be involved in the regulation of apoptosis. However, its apoptotic role is still debated and its participation in DNA replication is unknown. Here, we demonstrate that miR-630 inhibits cell proliferation by targeting cell-cycle kinase 7 (CDC7) kinase, but maintains the apoptotic balance by targeting multiple activators of apoptosis under genotoxic stress. We identified a novel regulatory mechanism of CDC7 gene expression, in which miR-630 downregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 55 publications
(93 reference statements)
1
44
1
Order By: Relevance
“…Previous reports have shown that miR-630 decreases apoptotic cell death by blocking PTEN expression but inhibits proliferation in breast and lung cancers [9–11]. In our study, miR-630 had no effect on proliferation.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous reports have shown that miR-630 decreases apoptotic cell death by blocking PTEN expression but inhibits proliferation in breast and lung cancers [9–11]. In our study, miR-630 had no effect on proliferation.…”
Section: Discussioncontrasting
confidence: 62%
“…These authors also showed that miR-630 was upregulated in a majority of ccRCC patients and that miR-630 expression was an independent prognostic factor for patients with renal cancer . Moreover, Cao et al (2014b) demonstrated that miR-630 targets CDC7, thereby inhibiting CDC7-mediated initiation of DNA synthesis and inducing G1 arrest. However, miR-630 has a bimodal role in the regulation of apoptosis because of its multiple target effects, which maintains apoptotic balance under genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN, which is wellknown for its role in tumor growth, invasion, and metastasis, has been reported as a tumor suppressor gene in ovarian cancer (Kurose et al, 2001;Lee and Park, 2009) with implications in ovarian cancer cell resistance to cisplatin (Wu et al, 2008b;Singh et al, 2013). MiR-630 gets involved in tumorigenesis by targeting different molecules such as BCL2, BCL2L2, CDC7, and IGF-1R (Galluzzi et al, 2010;Huang et al, 2011;Cao et al, 2014b). As an miRNA may possess multiple targets, we speculated that miR-630-induced cell proliferation and migration and that apoptosis may be linked to PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-630 inhibits cell proliferation by targeting cell-cycle kinase 7 (CDC7), but maintains the apoptotic balance by targeting multiple activators of apoptosis under genotoxic stress. On the one hand, miR-630 promotes apoptosis via blocking CDC7-mediated initiation of DNA synthesis; on the other hand, it reduces apoptosis by targeting several other apoptotic modulators such as PARP3, DDIT4, EP300 and EP300 downstream effector p53, thereby maintaining the apoptotic balance [26].…”
Section: Cddp Regulates Mirna Processingmentioning
confidence: 99%